Membangun Karakter Siswa Melalui Kegiatan Kepramukaan di SD Negeri 1 Parungkamal - Yuliyani, Devy Riri (Jurnal Pancar, 2018)
This research is motivated by the condition of education in Indonesia that cannot necessarily realize superior, intelligent and characterized human resources as expected. Moral problems faced by students become things that are centered as evidence of the erosion of character. Therefore, it takes effort to build student character, namely through Scouting activities. Solving in the Solving in the formulation of this problem uses a case study method with a qualitative approach with the subject namely SD N 1 Parungkamal students. The results obtained during the research, namely scouting activities is an independent learning process for students to develop themselves into a whole person. Scouting activities as non-formal education in the school education system are carried out in the open and prioritize various activities and skills rather than theories that can build personality and character that are noble, independent, caring, responsible, love water and have all life skills these types of personality characters are contained in the honor code of Paramuka namely Dasa Dharma Pramuka and Satya Pramuka.